Pregnancy with COVID-19 in Malaysia: A Case Series - Siti Hayati Mohd Nahwari; Bahiyah Abdullah; Suzanna Daud; Norhana Mohd Kassim (UiTM Press, 2021)
This case series highlights the outcome of four pregnancies complicated with COVID-19 as the pandemic of coronavirus disease 2019 (COVID-19) poses a lot of uncertainties due to lack of scientific evidence in guiding the management of pregnancy with COVID-19. The women were between 25 and 31 years of age and of 35 - 39 weeks of gestation with underlying no medical problems. Three women were delivered via caesarean section and one woman was delivered via ventouse delivery due to poor progress during the second stage of labour. Two women were in stage 4 of the disease (having breathing difficulties and requiring oxygen support) at presentations. One of them was treated with hydroxychloroquine (HC) only while another one was treated with both HC and antiviral medications; none required assisted ventilation during their hospitalizations. There is no vertical transmission of COVID-19 disease observed in this case series.